The impact of maturation on concentrations of key odour active compounds which determine the aroma of tequila - González-Robles, Ivonne Wendolyne; Cook, David J. (Wiley, 2016)
Samples of non-mature and añejo (matured) tequila of the same brand/provenance were analysed using GC–MS and gas chromatography olfactometry (GC-O)/aroma extract dilution analysis (AEDA) to provide quantitative data on the most odour active compounds that contribute to the aroma of these spirits. Extracts of non-mature tequila were characterized by 26 odour-active regions, which included ethyl hexanoate, ethyl octanoate, 2-phenylethyl acetate, β-damascenone, isoamyl alcohol and octanoic acid as the most odour-active compounds (flavour dilution, FD, factor ≥ 6561). In contrast, extracts of the mature spirit showed 36 odour-active zones, where the compounds with the highest FD factors (6561) were ethyl hexanoate, ethyl octanoate, 2-phenylethyl acetate, isoamyl alcohol, phenethyl alcohol, guaiacol, 4-ethyl guaiacol, vanillin, cis/trans whisky lactones, β-damascenone and octanoic acid. The aromagram of mature tequila was thus differentiated from that of the non-mature spirit owing to the presence of cask-extractive compounds and the increased FD factors of certain terpenes, higher alcohols and acetals. This study provides a comprehensive and quantitative understanding of changes in key odourants of tequila as a result of the maturation process and also reveals a further characterization of the likely impact of each compound on overall spirit flavour, in terms of odour activity values.